Development and Characterization of New Monoclonal Antibodies Against Porcine Interleukin-17A and Interferon-Gamma - Manirarora, Jean N.; Walker, Kristen E.; Patil, Veerupaxagouda; Renukaradhya, Gourapura J.; LaBresh, Joanna; Sullivan, Yvonne; Francis, Ore; Lunney, Joan K. (Frontiers in Immunology, 2022)
Current research efforts require a broad range of immune reagents, but those available for pigs are limited. The goal of this study was to generate priority immune reagents for pigs and pipeline them for marketing. Our efforts were aimed at the expression of soluble swine cytokines and the production of panels of monoclonal antibodies (mAbs) to these proteins. Swine interleukin-17A (IL-17A) and Interferon-gamma (IFNg) recombinant proteins were produced using yeast expression and used for monoclonal antibody (mAb) production resulting in panels of mAbs. We screened each mAb for cross-species reactivity with orthologues of porcine IL-17A or IFNg and checked for inhibition by other related mAbs, to assign mAb epitopes. For porcine IL-17A, a panel of 10 mAbs resulted in our assigning 8 different epitopes, with the dolphin exhibiting the highest cross-species reactivities. For porcine IFNg, a panel of 9 mAbs was characterized with 4 different epitopes; the highest cross-species reactions were found with dolphin, bovine, and caprine orthologues as well as a unique reaction of one mAb with zebrafish. The anti-IL-17A mAbs were used to develop a quantitative sandwich ELISA detecting the yeast expressed protein as well as native IL-17A in stimulated peripheral blood mononuclear cell (PBMC) supernatants. Our analyses showed that PMA/ionomycin stimulation of PBMC induced significant expression of IL-17A by CD3+ T cells by several of our mAbs. These new mAbs expand opportunities for immunology research in swine.